The comics of Chris Ware : drawing is a way of thinking (University Press of Mississippi, 2010)
Inventing cartooning ancestors : Ware and the comics canon / Jeet Heer -- Masked fathers : Jimmy Corrigan and the superheroic legacy / Jacob Brogan -- The limits of realism : alternative comics and middlebrow aesthetics in the anthologies of Chris Ware / Marc Singer -- Chris Ware's failures / David M. Ball -- Chris Ware and the burden of art history / Katherine Roeder -- In the comics workshop : Chris Ware and the oubapo / Martha B. Kuhlman -- Comics and the grammar of diagrams / Isaac Cates -- On modernism's ruins : the architecture of "Building stories" and lost buildings / Daniel Worden -- Chris Ware's "Building stories," gentrification, and the lives of/in houses / Matt Godbey -- Confronting the intersections of race, immigration, and representation in Chris Ware's comics / Joanna Davis-McElligatt -- Public and private histories in Chris Ware's Jimmy Corrigan / Shawn Gilmore -- Autobiography with two heads : Quimby the Mouse / Benjamin Widiss -- Chris Ware and the pursuit of slowness / Georgiana Banita -- Imagining an idiosyncratic belonging : representing disability in Chris Ware's "Building stories" / Margaret Fink Berman -- Past imperfect : "Building stories" and the art of memory / Peter R. Sattler